A perspective on the U.S.-Canada manufacturing productivity gap. - Eldridge, Lucy P.; Sherwood, Mark K. (Monthly Labor Review, 2001)
The writers discuss the different statistical methods used by the United States and Canada in calculating manufacturing productivity growth. They found that the methods used by the two countries were generally quite similar, and they concluded that a significant proportion of the difference in productivity performance can be attributed to the performance of the United States' information technology sector. The electronics industry and the machinery and computers industry contributed most to productivity growth in the United States, whereas the transportation industry in Canada helped reduce the size of the gap.